2007
DOI: 10.1021/la0636208
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Detection and Fingerprinting of Bacteria by Glass-Supported Lipid/Polydiacetylene Films

Abstract: Glass-supported films of lipids and polydiacetylene were applied for visual detection and colorimetric fingerprinting of bacteria. The sensor films comprise polydiacetylene domains serving as the chromatic reporter interspersed within lipid monolayers that function as a biomimetic membrane platform. The detection schemes are based on either visible blue-red transitions or fluorescence transformations of polydiacetylene, induced by amphiphilic molecules secreted by proliferating bacteria. An important feature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…Several studies with PDA films were reported in the literature. Scindia et al [16] developed glass-supported films of lipids and polydiacetylene for visual detection and colorimetric fingerprinting of bacteria. Meir et al [26] constructed agarose-embedded chromatic films to obtain color changes and fluorescence transformations in response to bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies with PDA films were reported in the literature. Scindia et al [16] developed glass-supported films of lipids and polydiacetylene for visual detection and colorimetric fingerprinting of bacteria. Meir et al [26] constructed agarose-embedded chromatic films to obtain color changes and fluorescence transformations in response to bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
“…New technologies of producing packaging with intelligent functions have been developed to fulfil the requirement of conscious consumers for freshness and safety food products [14][15][16]. Therefore, this research aims to develop a smart packaging with polydiacetylene system to detect Salmonella in foods using the approach of color changes.…”
Section: Introductionmentioning
confidence: 99%
“…The film can be studied by fluorescence microscopy if the molecules in the film contain chromophores that emit fluorescence. Scindia et al (2007) studied chromatic changes of PDA/phospholipids films in the presence of different bacteria. They demonstrated that significantly higher fluorescence emission signals were recorded from the film when solutions containing greater bacterial concentrations were in contact with the film.…”
Section: Characterization Of Pda Films and Vesiclesmentioning
confidence: 99%
“…The diacetylene monomers are spread on the water subphase in a chloroform (Scindia et al 2007) or chloroform/benzene solution (Carpick et al 2004). The films are incubated for a period at zero pressure prior to compression and then compressed until a condensed phase is attained.…”
Section: Characterization Of Pda Films and Vesiclesmentioning
confidence: 99%
“…Using the property, PCDA-based sensors have been developed to detect biological samples, such as bacteria and viruses. [24][25][26] Recently, innovative chemical modi¯cation of PCDA systems have exploited surface binding reactions, making PCDA vesicles for chromatic sensing of molecular recognition. 27,28 Herein, we developed a noninvasive, real-time and online analysis method using PCDA nanovesicles modi¯ed with HAA as receptor that could recognize the N-acetylgalactosamine containing Oglycans on Gal-de¯cient IgA1.…”
Section: Introductionmentioning
confidence: 99%